Improve germination of caper (Capparis Spinosa l.) seeds by different induction treatments of seed dormancy breaking - M. R. Labbafi; A. Mehrafarin; H. Naghdi Badi; M. Ghorbani; M. Tavakoli (Trakia Journal of Sciences)
Seed dormancy is a common phase of the plant life cycle; different treatments can be used for breaking dormancy. The aim of this study was to find the best treatment for breaking dormancy and improve germination of caper (Capparis spinosa L.). This study based on the completely randomized design (CRD) with 3 replications was done at research Laboratory of Medicinal Plants Institute, ACECR, Karaj, Iran. After different induction treatments containing different levels of potassium nitrate (KNO3), GA3, soaking and soaking with runner water, sulfuric acid, thidiazuron, and benzyl amino-purine, seeds were placed in Petri-dishes and incubated in two temperature regimes, first at fixed 20 ͦC, and second, alternate between 20 and 30 ͦC. The result showed that the germination percentage and germination rate of caper increased up to 75% and 1.35 respectively when the seeds treated with sulfuric acid for 15 min, and 2000 ppm GA3 under alternate 20-30 ͦC temperatures. Caper seed dormancy is mainly due to the inhibitors and hard seed coat that it prevents seed germination.